FORMATION OF THE STARTUP ECOSYSTEM AND ITS IMPACT ON ECONOMIC GROWTH - Rakhimova Shakhnоza Saparbayevna (Innovate Conferences, 2025)
The formation of a robust startup ecosystem is increasingly recognized as a key driver of sustainable economic growth, especially in developing countries. Startups contribute significantly to job creation, technological innovation and increased competitiveness by introducing new products, services and business models. A well-functioning ecosystem—comprising access to finance, mentorship, favorable regulations, skilled human capital and supportive infrastructure—plays a pivotal role in enabling startups to thrive. This paper examines the core components of startup ecosystems, the factors influencing their development and their direct and indirect impact on national and regional economic growth. Special attention is given to the challenges faced by emerging economies in nurturing such ecosystems and policy recommendations to enhance their effectiveness.
Keywords: startup ecosystem, economic growth, entrepreneurship, innovation, emerging markets, venture capital, business environment, job creation, policy support, technological development.